The Effect Of Green Perceived Value, Green Perceived Risk And Green Trust To Green Purchase Intention Product Of The Body Shop - Pratama, Yo Tendy, Prof. Dr. Wahyuddin, M.S (2015)
The purpose of this study is to develop a framework to explore the influence of the original green perceived value and green perceived risk on green purchase intention of and to discuss the mediating role of green trust and also explore positive and negative influence. This study applies four original concepts - green perceived value, green perceived risk, green trust, and green purchase intentions - to develop an integral model to enhance green purchase intentions. In addition, this research employs an empirical study by means of the questionnaire survey method to verify the hypotheses and to explore its managerial implications. Structural equation modeling (SEM) is applied to verify the research framework. The empirical results show that perceived value will positively affect trust green and green purchase intention, while perceived risk negatively affects the good green from them. Furthermore, this study shows that the relationship between purchase intention of green and two of their predecessors - the green felt values and perceived risks of green - the green partially mediated by trust. Therefore, environmentally friendly goods with efficient marketing to increase the perceived value of the green and to reduce the perceived risk is beneficial to increase the confidence of green and green purchase intention. This study summarizes the literature on green marketing and relationship marketing into new managerial framework of green purchase intention. It uses four new construction - green perceived value, green perceived risk, green trust, and green purchase intention - to develop original research framework to improve the green purchase intention. therefore, this paper develops a framework of research intentions to purchase environmentally friendly goods marketing are fairly efficient way of marketing and filling gaps in the research.